2004
DOI: 10.1111/j.1741-2358.2004.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status and change in handgrip strength over a 5‐year period in 80‐year‐old people

Abstract: The presence of oral inflammation may lead to loss in muscle strength increasing the risk of disability. Therefore, good dental care throughout the life span may decrease risk of disability in old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
100
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(116 citation statements)
references
References 27 publications
9
100
3
4
Order By: Relevance
“…The results support previous research that links poor dentition to physical impairments [6, 810, 15, 16]. Tooth loss may be an indicator of low physiological reserve [29] resulting from cumulative effects of unfavorable exposures throughout the life course, which also has adverse effects on walking speed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results support previous research that links poor dentition to physical impairments [6, 810, 15, 16]. Tooth loss may be an indicator of low physiological reserve [29] resulting from cumulative effects of unfavorable exposures throughout the life course, which also has adverse effects on walking speed.…”
Section: Discussionsupporting
confidence: 88%
“…So far, few studies have examined longitudinal associations between oral health and physical function. Prospective studies have shown that periodontitis and tooth loss are associated with decline in physical functions such as balance and muscle strength [15, 16], and incident disability [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HGS was found to be significantly correlated with the strength and power of the muscles of the lower limbs, the cross-sectional size of the Achilles tendon, and knee bending torque 23. Hämäläinen et al observed a correlation between HGS and the number of teeth present in a group of elderly men, but they did not find an association between the number of teeth and change in HGS over the course of 5 years of follow-up 7. We have not found association between masticatory muscles activity and HGS, although in our previously conducted study, HGS was positively correlated with strong masseter muscle tension 24…”
Section: Discussionmentioning
confidence: 98%
“…Handheld dynamometry and bioelectrical impedance analysis provide a valid and reliable measurement of muscle strength and muscle mass, respectively 6. Missing teeth might be the measure of the past appearance of oral inflammation 7. One of the most commonly applied measurements of nutritional status is BMI.…”
Section: Introductionmentioning
confidence: 99%
“…People with periodontitis are at increased risk of oral pain and tooth loss, which leads to limited oral function such as eating, swallowing, and speaking (Furuta & Yamashita, 2013). Poor oral health is related to decreased functional ability and physical fitness and decreased dietary intakes and variety (Hamalainen, Rantanen, Keskinen, & Meurman, 2004; Iwasaki et al, 2014; Iwasaki et al, 2015). Periodontitis also may cause halitosis, which can negatively impact on daily life activities such as socializing and communication with other people (Azodo, Onyeagba, & Odai, 2011).…”
Section: Discussionmentioning
confidence: 99%